Data clustering and its Application to numerical function optimization algorithm (International Journal of Advanced Research in Computer Science, 2017)
This paper present a novel technique of Artificial Intelligence (swarm), specifically teaching learning based optimization (TLBO), it is a nature inspired algorithm and based on two parameters i.e. Teacher phase and Learner Phase. These modes are the base for the teaching learning based optimization. Experimental results using various benchmarks mathematical function show that TLBO has improved performance than PSO and other optimization algorithm. Keywords: Function, Optimization, Teaching and Learning Mode, clustering, TLB, Evolutionary algorithms; Swarm intelligence based algorithms, Unconstrained benchmark functions